An MMC based HVDC system with optimized AC fault ride-through capability and enhanced circulating current suppression control - Badar, Jahangeer; Akhtar, Faheem; Kumar, Dileep; Munir, Hafiz Mudassir; Ali, Khawaja Haider; Alsaif, Faisal; Alsulamy, Sager (Frontiers in Energy Research, 2023)
Modular multilevel converter (MMC) is a proven technology for HVDC applications due to its salient features such as modularity and excellent power quality. To ensure best possible grid support, recent grid codes require incorporating fault ride-through (FRT) strategies so that HVDC converter stations remain connected and maintain reliable operation under various symmetrical and asymmetrical AC faults. In this paper, a communication-free enhanced FRT technique without the need of DC chopper has been proposed. The proposed FRT strategy ensures quick post fault recovery operation and can effectively manage DC link and capacitor voltages within safe limits. Along with proposed FRT strategy, in order to avoid high circulating current (CC) inside an MMC, this paper has proposed an optimal CC control approach based on PR and PI controllers in an abc reference frame. The suggested technique lowers the ripple in capacitor voltages while reducing the magnitude of the CC. Under both balanced and unbalanced ac grid conditions, the ripple in the dc link voltage is also reduced without the use of dual synchronous reference frame (DSRF) or any additional controllers. Simulation results confirm the effectiveness of the proposed FRT and CC suppression techniques for a 580-kV, 850-MW MMC-based HVDC system.